Native Americans and the U.S. government - Blakely, Martha (New York : Chelsea Juniors, 1995)
Discusses the history of the United States government's relations with the Native Americans.
School Library Journal
Booklist
Multicultural Review
7.0
3-6
Keywords: Indians of North America; Indians of North America